Does How We Feel About Financial Strain Matter for Mental Health? - Sarah D. Asebedo; Melissa J. Wilmarth (Journal of Financial Therapy, 2017)
This study investigated how stress responses to financial strain are related to mental health (i.e., depression) to answer the question: Does how we feel about financial strain matter? Informed by the ABC-X model of family stress and analyzed with data from the Health and Retirement Study (HRS), results reveal that financial strain is significantly related to increased depression; however, financial stress was found to moderate this relationship. Financially strained respondents without a stress response did not have significantly different depression scores than those who were not experiencing financial strain; however, depression scores increased as the stress response to financial strain increased. Consistent with the ABC-X model, results suggest that financial strain is a neutral event until it is processed and interpreted by an individual, with subjective perceptions a more powerful predictor of mental health than objective financial circumstances. These results emphasize an area of synergy for financial and mental health researchers and professionals.
Keywords: Financial stress; Financial stressors; Financial strain; Mental health; Depression